Reducing agricultural nitrogen use: A price endogenous partial equilibrium analysis in the Yangtze River Basin, China - Yu, S.; Fan, S.; Ti, C.; Ma, Y. (Frontiers in Environmental Science, 2022)
The overuse of nitrogen fertilizer in agricultural production has been a considerable issue in China, resulting in negative impacts on environment. Reducing agricultural nitrogen use thereby, has become one of the top proprieties in achieving sustainable development goals in Chinese agricultural sector. Searching for effective approaches to reduce nitrogen use are essential to agricultural and environmental sustainability. In this paper, we selected the Yangtze River Basin as study area due to its critical role in Chinese agricultural production, and established a price endogenous partial equilibrium model to simulate the reducing effects on nitrogen use from nitrogen use optimization (NUO) and nitrogen use efficiency improvement (NUE+). Based on the agricultural datasets derived in the year of 2019, simulation results revealed that: (1) NUO helps to reduce nitrogen use and nitrogen loss by 6.99% and 7.50%, respectively, if considering the changes in acreages, the reducing effect would become less significant; (2) nitrogen use will continuously decrease with the improvement of NUE, the reducing rates are 7.85%, 15.38%, 22.65% and 28.02% under NUE+10%, NUE+20%, NUE+30% and NUE+40% scenarios, nitrogen loss is more sensitive; (3) crop heterogeneities indicate that cereals are regarded as nitrogen overused crops and perform more sensitive in reducing nitrogen use under NUE+ scenarios than oil crops. Accordingly, this study suggests that policies and incentives in practice on NUO and NUE improvement are necessary, and flexible adjustment strategies of crop planting structures, such as enlarging acreage in cereals, might be useful in reducing nitrogen use in the Yangtze River Basin.